Convergent and Divergent Structural Connectivity of Brain White Matter Network Between Patients With Erectile Dysfunction and Premature Ejaculation: A Graph Theory Analysis Study - Zhang, Tielong; Yuan, Peng; Cui, Yonghua; Yuan, Weibiao; Jiang, Daye (Frontiers in Neurology, 2022)
Background: Sexual dysfunction, including erectile dysfunction (ED) and premature ejaculation (PE), have been found to be associated with abnormal structural connectivity in the brain. Previous studies have mainly focused on single disorder, however, convergent and divergent structural connectivity patterns of the brain network between ED and PE remain poorly understood. Methods: T1-weighted structural data and diffusion tensor imaging data of 28 psychological ED patients, 28 lifelong PE (LPE) patients and 28 healthy controls (HCs) were obtained to map the white matter brain networks. Then the graph theoretical method was applied to investigate the differences of network properties (small-world measures) of the WM network between ED and LPE patients. Furthermore, nodal segregative and integrative parameters (nodal clustering coefficient and characteristic path length) were also explored between these patients. Results: Small-world architecture of the brain networks were identified for both psychological ED and LPE groups. However, ED patients exhibited increased average characteristic path length of the brain network when compared with LPE patients and HCs. No significant difference was found in the average characteristic path length between LPE patients and HCs. Moreover, increased nodal characteristic path length was found in the right middle frontal gyrus (orbital part) of ED and LPE patients when compared with HCs. In addition, ED patients had increased nodal characteristic path length in the right middle frontal gyrus (orbital part) when compared with LPE patients. Conclusions: Together, our results demonstrated that decreased integration of the right middle frontal gyrus (orbital part) might be a convergent neuropathological basis for both psychological ED and LPE. In addition, ED patients also exhibited decreased integration in whole WM brain network, which was not found in LPE patients. Therefore, altered integration of the whole brain network might be the divergent structural connectivity patterns for psychological ED and LPE.